A cognitive rhetorical approach to Basque proverbs: analogical mappings in coordination - Garai, Koldo J. (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 2013)
In this work, different occurrences of the connective "and" in some Basque proverbs gathered in the 16th and 19th centuries are studied. "And" appears in grammatically definable types of constructions beyond pragmatic ambiguity; the environments where "and" occurs show a fixed pattern linked to a conceptual structure. This work focuses on the less fixed pattern of the typology "A and B is Y", where the first term mentioned "A" is defined in terms of the second "B" demonstrating the important role played by analogy. There is also a complex variety of coordinated proverbs, which link two seemingly independent proverbs; in these proverbs "and" provokes a shift in point of view of the fictional utterer. The evaluative string (Y) poses the question of the directionality of the proverb, when there are variants of the same proverb, one of them lacking the string, what the presupposition range of the given cultural milieu is, from Honeck’s (1997) "Generic Ideals" to Kay’s (1996) "context proposition". The methodology is based on Turner and Fauconnier’s Blending Theory (1998) and Conceptual Integration Networks (Turner & Fauconnier 2001), and on contemporary Rhetoric of Argument (Perelman & Olbrechts-Tyteca), The simple type of proverbs falls either under the category of "one-sided shared organizing topology" or under the category of "unfilled shared topology network". In the complex type of proverbs, two asymmetric spaces are linked, but analogously to the simple type, the second part of the proverb constraints the meaning of the first part. Two alternative space configurations for proverb understanding are provided.